Work and wellbeing outcomes for LGBT+ employees perceiving a calling: the role of diversity climate - West, Danielle, author; Gardner, Danielle, advisor; Dik, Bryan, committee member; Amberg, Martha, committee member; Peila-Shuster, Jackie, committee member (Colorado State University. Libraries, 2025)
Work as Calling Theory (WCT; Duffy et al., 2018) discusses the benefits and consequences that perceiving a calling can provide. For working individuals, perceiving a calling is associated with better work- and wellbeing-related outcomes (Esteves & Lopes, 2016; Duffy & Dik, 2013). One population that has not been well researched in terms of vocational calling are gender and sexual minority employees, or those with a LGBT+ identity (Velez et al., 2021). A positive diversity climate at work is an important factor for LGBT+ employees' experience with work, as Signaling Theory (Spence, 1973) suggests organizations provide signals that convey their intentions or feelings regarding LGBT+ employees (Webster et al., 2018). These signals inform employee perceptions of the organization's diversity climate, and may further play a role in how perceiving a calling predicts outcomes for LGBT+ employees. This study explored the hypothesized role of diversity climate perceptions in supporting LGBT+ employees' work and wellbeing outcomes from perceiving their calling. This study used select variables from a broader, three timepoint data collection of 404 LGBT+-identifying participants recruited from Prolific. Results supported the notion that perceiving a calling in LGBT+ employees was associated with greater job satisfaction and satisfaction with life, and lowered turnover intentions and burnout. A stronger perceived diversity climate at work was also associated with an increased sense of job satisfaction and satisfaction with life, and lowered turnover intentions and burnout. Results also supported that perceiving a calling more strongly negatively predicted turnover intentions for LGBT+ employees working in a stronger (versus weaker) diversity climate. This study contributes towards the understanding of how perceiving a calling relates to LGBT+ employee experiences under the WCT model, underscoring the benefits of perceived calling as impactful and worthy of encouragement. The results are also impactful for organizations in demonstrating that creating an inclusive diversity climate is a meaningful endeavor toward fostering better work and wellbeing experiences for LGBT+ employees.
Keywords: calling; LGBT+ employees; turnover intentions; diversity climate; burnout; satisfaction with life